Expression and Clinical Significance of Computer-aided HIC-1 in Colon Cancer. (April 2020) - Yuan, Heng; Hu, Zhenliang; Luo, Wenqi; Liu, Guanlan
Abstract: Objective: To investigate the expression and clinical significance of HIC-1 in colon cancer. Methods: RT-PCR, immunohistochemistry, and computer image analysis were used to detect the expression levels of HIC-1 gene and protein in 200 patients with colon cancer and the corresponding paracancerous tissues to analyze the relationship between the expressions and clinicopathological characteristics as well as their correlation. Results: the expression of HIC-1 mRNA was up-regulated in the colon cancerous tissues of 141 patients (70.5%) and in the paracancerous tissues of 21 patients (10.5%) with colon cancer, and the difference was statistically significant (P = 0.001). The expression of HIC-1 mRNA was correlated with Dukes stage, lymph node metastasis, and differentiation degree. The up-regulated expression of HIC-1 mRNA in colon cancer and the corresponding paracancerous tissues were 104 (52.0%) and 121 (60.5%), respectively. The expression of HIC-1 mRNA was not correlated with any clinicopathological characteristics of colon cancer. The immunohistochemical staining intensity of HIC-1 in cancerous tissues was 1.79 ± 0.11, higher than that in paracancerous tissues (P = 0.002). The expression level of HIC-1 was correlated with Dukes stage and lymph node metastasis. The expression of HIC-1 in colon cancerous and paracancerous tissues was weaker than that of HIC-1, which was not correlated with clinicopathological characteristics. There was a negative correlation between the expression of computer-aided and HIC-1 in colon cancerous tissues (r = -0.63, P < 0.01). Conclusions: The expression of HIC-1 can promote the progression of colon cancer, and it may have an antagonistic effect.